The Impact of Lifestyle on Online Purchasing Decisions and Repurchase Intentions of Shopee Customers - Syafriya, Indra; Lahindah, Laura (Devotion : Journal of Research and Community Service, 2024)
Purchasing decisions because many factors can influence how buyers act towards products or services. When buyers want to buy something, they have to go through several stages. The initial stage is problem recognition, where they know what they need. Once they know what they need, they will be encouraged to seek additional information to meet their needs. Each person has unique characteristics. There are different cultures, ages, educations, jobs, activities, and hobbies. Producers must be able to steal the attention of various consumers so that the goods they sell are purchased. Marketers must understand consumer behavior, actions and ways of thinking so they can create effective marketing strategies. Consumers will respond to marketers' actions if they have the right strategy. The ability to compete increases when marketers take over the study of consumer behavior. There are several components that influence repurchase intentions, namely 1. Consumer satisfaction: if customers are satisfied with the services provided, the company will become better in the eyes of customers, reduce purchasing costs, reduce failure costs, increase profits, and reduce trial and error purchases. so customers will prefer to buy again. 2. Brand preferences: brands are constituents of differentiation attributes that influence customers' perceptions of what they buy.